Hexapod with legs based on Peaucellier–Lipkin mechanisms: A mathematical structure used in reconfiguration for path planning. (31st August 2018) - Juárez-Campos, Ignacio; Núñez-Altamirano, Diego A; Márquez-Pérez, Lucia; Romero-Muñoz, Leonardo; Juárez-Campos, Beatriz
This article describes the way in which six nontraditional legs collaborate to provide locomotion to a walking machine when it moves along a path. Such legs are based on the one-degree-of-freedom Peaucellier–Lipkin mechanism, which was modified by the addition of four degrees of freedom. Such five-degree-of-freedom legs have the ability to adapt their postures according to the center of rotation around of which the machine walks. The attributes and abilities of the hexapod are expressed by means of a mathematical framework, which grants the spatial description and required joint variables, according to a specific task, resulting in the configuration of its legs for a particular path planning. Additionally, the article presents an illustrative example describing a detailed procedure concerning the configurations and collaboration of their legs according to an imposed center of rotation around of which the six-legged robot walks.